Transforming Bullying Prevention Through Assertive Communication Training - Quraini, Novi Ummul; Fatmawanti, Zaki Nur (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Bullying is a pervasive issue in educational settings, often resulting in physical and psychological harm to victims. It typically arises from a power imbalance, with aggressors seeking personal satisfaction through intimidation. Specific Background: This study addresses the effectiveness of psychoeducational interventions aimed at improving assertive communication skills among junior high school students, specifically at SMPN 5 Sidoarjo, to prevent bullying behaviors. Knowledge Gap: While previous research has explored bullying prevention strategies, there is limited empirical evidence demonstrating the impact of assertive communication training in Indonesian junior high schools. Aims: This research aims to evaluate the effectiveness of a structured psychoeducational program on students’ understanding and application of assertive communication to mitigate bullying. Results: Utilizing a quantitative experimental design with pre-test and post-test assessments, the study reveals a statistically significant improvement in assertive communication skills, evidenced by a Wilcoxon signed-rank test (p = 0.001) and a large effect size (r = 0.898). Novelty: This study contributes novel insights into the role of assertive communication training as a proactive approach to bullying prevention within the Indonesian educational context. Implications: The findings suggest that psychoeducational programs can effectively enhance students’ assertive communication abilities, highlighting the need for continuous training to deepen understanding and application. Ongoing psychoeducational efforts are recommended to foster a supportive and respectful school environment, ultimately reducing bullying incidents. Highlights: Improvement: Assertive communication significantly increased after psychoeducation. Effectiveness: Psychoeducation is essential for preventing bullying. Recommendation: Ongoing training needed for sustained communication skills. Keywords: Bullying, Assertive Communication, Psychoeducation, Junior High School, Prevention